Long-term outcome of pregnancy complicating with severe aplastic anemia under supportive care - Kuan-Ju Chen; Yao-Lung Chang; Horng Chang; Shen-Yuan Su; Hsiu-Huei Peng; Shuenn-Dyh Chang; An-Shine Chao (Elsevier, 2017)
Objectives: Pregnancy associated with aplastic anemia (AA) is a rare and heterogeneous disorder. We aimed to identify and evaluate the maternal and pregnant outcomes of pregnancy-associated severe AA treated with supportive care. Materials and methods: A 25-year retrospective study was conducted at in a single center between 1990 and 2014 with pregnancy associated severe AA. In addition, relevant published cases of antenatally diagnosed pregnancy-associated severe AA after 1990 were identified by PubMed. The main goal was to determine the impact of various risk factors on maternal and fetal outcomes. Results: 15 women with 18 pregnancies were enrolled. With addition of the published reports in literature, a total of 36 cases were included for reference review. Univariate analysis showed that low platelet counts (<2.0 × 109/L), bone marrow hypocellularity (<25%), and late diagnosis during pregnancy were predictors of poor maternal outcomes (P < 0.05). The complication rate of pregnancy outcomes was 53.3%, including preterm delivery, small gestational age (SGA), preterm premature ruptured of membranes (PPROM) and preeclampsia. Conclusions: This study identified the risk factors of mortality and morbidity in pregnant women with severe AA, as well as the obstetrical complications associated with neonatal outcome.